A Comprehensive Update on the Chylomicronemia Syndrome - Goldberg, Ronald B.; Chait, Alan (Frontiers in Endocrinology, 2020)
The chylomicronemia syndrome is characterized by severe hypertriglyceridemia and fasting chylomicronemia and predisposes affected individuals to acute pancreatitis. When due to very rare monogenic mutations in the genes encoding the enzyme, lipoprotein lipase, or its regulators, apo C-ll, apo -V, GPIHBP1, LMF1 and CERBH, it is referred to as the familial chylomicronemia syndrome. Much more frequently, the chylomicronemia syndrome results from a cluster of minor genetic variants causing polygenic hypertriglyceridemia, which is exacerbated by conditions or medications which increase triglyceride levels beyond the saturation point of triglyceride removal systems. This situation is termed the multifactorial chylomicronemia syndrome. These aggravating factors include common conditions such as uncontrolled diabetes, overweight and obesity, alcohol excess, chronic kidney disease and pregnancy and several medications, including diuretics, non-selective beta blockers, estrogenic compounds, corticosteroids, protease inhibitors, immunosuppressives, antipsychotics, antidepressants, retinoids, L-asparaginase and propofol. A third uncommon cause of the chylomicronemia syndrome is familial forms of partial lipodystrophy. Development of pancreatitis is the most feared complication of the chylomicronemia syndrome, but the risk of cardiovascular disease as well as non-alcoholic steatohepatitis is also increased. Treatment consists of dietary fat restriction and weight reduction combined with the use of triglyceride lowering medications such as fibrates, omega 3 fatty acids and niacin. Effective management of aggravating factors such as improving diabetes control, discontinuing alcohol and replacing or reducing the dose of medications that raise triglyceride levels is essential. Importantly, many if not most cases of the chylomicronemia syndrome can be prevented by effective identification of polygenic hypertriglyceridemia in people with conditions that increase its likelihood or before starting medications that may increase triglyceride levels. Several new pharmacotherapeutic agents are being tested that are likely to considerably improve treatment of hypertriglyceridemia in people at risk.